SAT0204 The Eular Systemic Sclerosis Impact of Disease (ScleroID) Score – A New Patient-Reported Outcome Measure for Patients with Systemic Sclerosis under Development. (15th July 2016) - Dobrota, R.; Becker, M.; Fligelstone, K.; Fransen, J.; Kennedy, A.; Allanore, Y.; Carreira, P.; Czirijak, L.; Denton, C.; Hesselstrand, R.; Sandqvist, G.; Kowal-Bielecka, O.; et al.
Abstract : Background: Patient reported outcome measures (PROM) are required as key outcomes in disease modifying therapeutic trials in systemic sclerosis (SSc) and could also improve the clinical care of patients with SSc. A PROM tool for clinical trials and practice in SSc, covering the different features of this multi-organ autoimmune disease, is lacking. Objectives: To develop and validate a brief, disease-specific, patient-derived, composite disease impact score for scientific and clinical use in SSc. Methods: This multi-center project involves SSc patients and experts from 11 European countries. Firstly, using the nominal group technique, patients with SSc selected the health dimensions where the disease has the most significant impact. The dimensions were subsequently given numeric priority by an international group of SSc patients. The dimensions with the top 10 median ranks, as ranked by the patients, were used to construct the ScleroID questionnaire using numeric rating scales. Further, the dimensions are currently weighted by distributing 100 points among the dimensions by a larger cohort of patients from all participating countries. The calculation of the score will be based on the ranking of the weights. Results: 24 SSc patients selected 17 health dimensions in the nominal group exercise. The prioritization cohort included 108 SSc patients from 11 centers (female:male 82:25, limited:diffuse SSc subset 53:54). The top 10 health dimensions which were ranked most relevant by the patients were Raynaud's phenomenon, hand function, upper and lower gastrointestinal tract symptoms, pain, fatigue, limitation of life choices and activities, body mobility, breathlessness and digital ulcers (Figure 1 ). Conclusions: The EULAR ScleroID score is a novel tool under development designed for use in clinical practice and clinical trials to display the disease impact of SSc. Further validation of this new instrument will be performed as soon as the weighting procedure is completed. Acknowledgement: Contributing patients: Yanne Perriault, Susanne Tuppeck, Helene Kambourakis, Elisabeth Scheel, Stephan Houbertz, Anna Vegh, Beata Garay Toth, Barbara Zappitello, Grazia Tassini, Silvia Sandulescu, Ana Marcela Badea, Stefana Dumitru, Rachida Amrouch, Alicia García Oliva, Begoña María Gorricho Corta, Heleen Lever, Johanna Berglind, Mervat Gaafar, Natalie Perruchoud, Alice Martins Correia, Richard Dodds, Nicola Whitehill. Disclosure of Interest: R. Dobrota: None declared, M. Becker: None declared, K. Fligelstone: None declared, J. Fransen: None declared, A. Kennedy: None declared, Y. Allanore Grant/research support from: Bristol-Myers Squibb, Roche/Genentech, Inventiva, Pfizer, Sanofi, and Servier, Consultant for: Actelion, Bayer, Roche/Genentech, Inventiva, Medac, Pfizer, Sanofi, Servier, and UCB, P. Carreira: None declared, L. Czirijak: None declared, C. Denton: None declared, R. Hesselstrand: None declared, G. Sandqvist: None declared, O. Kowal-Bielecka: None declared, M. Matucci-Cerinic: None declared, C. Mihai: None declared, A. Gheorghiu: None declared, U. Müller-Ladner: None declared, M. Frerix: None declared, T. Heiberg: None declared, O. Distler Grant/research support from: Bayer, Sanofi, Ergonex, Boehringer Ingelheim, Actelion, Pfizer, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, EpiPharm, Ergonex, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, MedImmune, Pharmacyclics, Pfizer, Serodapharm, Sinoxa